Raccoon (Procyon lotor) Activity is Better Predicted by Water Availability than Land Cover in a Moderately Fragmented Landscape - Heske, Edward J.; Ahlers, Adam A. (My University, 2017)
Procyon lotor (Raccoon) is a habitat and dietary generalist that reaches its greatest population densities in heterogeneous, moderately fragmented landscapes. Even within such landscapes, a variety of natural and anthropogenic habitat variables can influence the local activity of Raccoons, and therefore their potential impact as nest predators. We examined Raccoon activity at 34 baited track-stations over 3 summers in forested ravines in the Shawnee National Forest (SNF), IL. We found that the dependability of water at a survey site was the best predictor of Raccoon activity, overshadowing any potential influences of land cover in the surrounding landscape. Landscape-level effects on Raccoon population size and density are likely widespread throughout moderately fragmented regions like the SNF, but variation in local activity can be predicted by the distribution of critical resources (e.g., water, den sites).
Citation: Heske, E. J., & Ahlers, A. A. (2016). Raccoon (Procyon lotor) Activity is Better Predicted by Water Availability than Land Cover in a Moderately Fragmented Landscape. Northeastern Naturalist, 23(3), 352-363. doi:10.1656/045.023.0302
Citation: Heske, E., and Ahlers, A. (2016). Raccoon (Procyon lotor) Activity is Better Predicted by Water Availability than Land Cover in a Moderately Fragmented Landscape. Northeastern Naturalist, 23(3), 352-363. https://doi.org/10.1656/045.023.0302